Feeling Socially Connected and Focusing on Growth: Relationships With Wellbeing During a Major Holiday in the COVID-19 Pandemic - Vaughn, Leigh Ann; Burkins, Patricia G.; Chalachan, Rachael D.; Judd, Janak K.; Garvey, Chase A.; Luginsland, John W. (Frontiers in Psychology, 2021)
Numerous major holidays celebrate socially gathering in person. However, in major holidays that happened during the pandemic, desires to nurture relationships and maintain holiday traditions often conflicted with physical distancing and other measures to protect against COVID-19. The current research sought to understand wellbeing during American Thanksgiving in 2020, which happened 8months into the COVID-19 pandemic, after months of physical distancing and stay-at-home orders. American Thanksgiving is a major holiday not limited to any religion. We asked 404 American adults how they spent Thanksgiving Day and to report on their experiences of that day. Predictors of wellbeing that we drew from self-determination theory were satisfaction of the fundamental needs for social connection (relatedness), for doing what one really wants (autonomy), and feeling effective (competence). The predictors of wellbeing that we drew from regulatory focus theory were a focus on growth (promotion), and a focus on security (prevention). We found that feeling socially connected and focusing on growth related most strongly to wellbeing. Additionally, participants who saw even one other person face-to-face reported significantly higher relatedness satisfaction, promotion focus, and wellbeing than those who did not. Our research could help construct persuasive messages that encourage nurturing close relationships at major holidays while remaining safe against the virus.